Caracterización de Habilidades Sociales en Estudiantes de Primer, Segundo y Tercer Semestre de los Programas: Administración, Ingeniería y Psicología de la Universidad Antonio Nariño. - Sánchez Cortes, William Andrés (Universidad Antonio Nariño, 2024)
Based on the knowledge that the HH.SS that are given from personal relationships, this work aims to measure the range of skills of a group of first, second and third semester students of the Administration, Engineering and Psychology programs of the Universidad Antonio Nariño, where the need was found to generate strategies that allow people to develop HH.SS, to avoid the generation of social maladjustment, as well as to encourage students to have excellent skills, in order to adapt to the demanding demands of the field productive; As a methodology, a quantitative type of cross-sectional non-experimental design with a descriptive scope was used and the HH.SS Evaluation Scale was applied as an instrument, then the results of the test were contrasted and discussed in relation to the theoretical underpinnings that study the subject; It is concluded by critically analyzing the repercussions of the deficit or appropriate HH.SS repertoire, where it was possible to establish the type of skills that the participants had in addition to identifying their strengths in relation to the different daily tasks, these results are discussed in relation to the impact of the student's skills training on their adaptation to the work world.